Phase equilibria in the Fe-Mo-Ti ternary system at 1000 °C. (November 2016) - Knowles, A.J.; Jones, N.G.; Messé, O.M.D.M.; Barnard, J.S.; Jones, C.N.; Stone, H.J.
Abstract: An isothermal section of the Fe-Mo-Ti ternary system at 1000 °C has been constructed using data acquired from a series of seven alloys. The limit of solubility of Fe in the continuous A2 phase field between Ti and Mo has been determined, as have the extents to which Mo may be accommodated in the B2 TiFe phase, and Ti in the D85 Fe7 Mo6 phase. The B2, D85 and C14 Fe2 (Ti, Mo) intermetallics were found to have limited tolerance for non-stoichiometric compositions. The positions of the A2 + B2 + C14 and A2 + C14 + D85 three-phase fields were determined, along with the extents of the A2 + B2, A2 + D85, A2 + C14, C14 + B2 and C14 + D85 two-phase fields. No ternary phases were observed in any of the alloys studied. Highlights: Phase equilibria in (Mo, Ti)-rich region of the Mo-Ti-Fe system established Extent of A2 + B2 + C14 and A2 + C14 + D85 phase fields determined A2 + B2, A2 + D85, A2 + C14, C14 + B2 and C14 + D85 two-phase fields seen Large A2 + B2 (Mo, Ti)-TiFe two-phase field identified for future alloy design